A large‐scale expression strategy for multimeric extracellular protein complexes using Drosophila S2 cells and its application to the recombinant expression of heterodimeric ligand‐binding domains of taste receptor. (6th September 2017) - Yamashita, Atsuko; Nango, Eriko; Ashikawa, Yuji
Abstract: Many of the extracellular proteins or extracellular domains of plasma membrane proteins exist or function as homo‐ or heteromeric multimer protein complexes. Successful recombinant production of such proteins is often achieved by co‐expression of the components using eukaryotic cells via the secretory pathway. Here we report a strategy addressing large‐scale expression of hetero‐multimeric extracellular domains of plasma membrane proteins and its application to the extracellular domains of a taste receptor. The target receptor consists of a heterodimer of T1r2 and T1r3 proteins, and their extracellular ligand binding domains (LBDs) are responsible for the perception of major taste substances. However, despite the functional importance, recombinant production of the heterodimeric proteins has so far been unsuccessful. We achieved the successful preparation of the heterodimeric LBD by use of Drosophila S2 cells, which have a high secretory capacity, and by the establishment of a stable high‐expression clone producing both subunits at a comparable level. The method overcame the problems encountered in the conventional transient expression of the receptor protein in insect cells using baculovirus or vector lipofection, which failed in the proper heterodimer production because of the biased expression of T1r3LBD over T1r2LBD. The large‐scale expression methodology reported here may serve as one of the considerable strategies for the preparation of multimeric extracellular protein complexes.